Prevalence and Public Health Importance of Cystcercus.bovis from Cattle Slaughtered in Mekelle Municipal Abattoir, Tigray, Ethiopia (Global Journal of Science Frontier Research, 2016)
A cross sectional study was conducted from November 2015 to March 2016 to estimate the prevalence of Cysticercosis, to investigate prevalence and rate C.bovis infection with in different risk factors and to determine the distribution and viability of cysts in organs of animals slaughtered in Mekelle municipal abattoir. Ante-mortem and postmortem examination based on the standard and routine procedure were performed on randomly selected apparently healthy cattle brought for slaughter during period of the study. Of the total 312 inspected animals, 21 animals were found infected with C. bovis distributed in different anatomical structures with an overall prevalence of 6.7% (21/312). Even though there is no statistical significant difference among different ages groups, sex, breed and body condition score of the animals, the prevalence was roughly varied. Relatively higher prevalence of infection was found in adult 15(71.4%) than that of old 6 (28.6%). Generally prevalence of Cysticercos is bovis was prominent in males 20(95.2) unlike female animals 1(4.8). About 269(86.2 %) examined animals were local breed with considerably higher prevalence 20(95.2%). Based on body condition score, reasonably greater prevalence was found in good body condition animals 10(47.6) followed by 8(38.1) and 3(14.3) in medium and poor conditioned animals, respectively. Noticeably higher number 234(75%) of cattle slaughtered in Mekelle abattoir came from highland area with fairly increased prevalence 15(71.4%). Moderately higher rate of infection was recorded within old cattle 8.8% (6/68) compare to adult animals 6.15 %( 15/244). Regarding cyst locations, out of the total 21 cattle positive for C. bovis, carcasses of 12 cattle were having the cysts at one site only and 9 at more than one site. More cysts were encountered in tongue. From a total of 21 identified cyst positive carcasess 6 were containeda viable cyst. The overall findings of this study indicated the importance of C
Keywords: abattoir; cattle; cbovis; cross sectional; mekelle; prevalence